Heart failure compromises muscle power of lower limbs of sedentary elderly people (Research, Society and Development, 2021)
Purpose. To analyze and to compare the absolute and relative muscle power of the lower limbs in sedentary elderly subjects with and without heart failure. Methods. The study included 36 elderly subjects (72 ± 6.5 years, 76.8 ± 4.8 kg, 171 ± 9.4 cm) divided into two groups: sixteen patients with heart failure versus twenty patients with coronary artery disease, but without heart failure. The muscle power of the lower limbs was assessed with a half-squat exercise; three repetitions were performed with three seconds of the interval between repetitions as fast as possible in the concentric phase. For the statistical analysis, unpaired Student's t-tests were used to compare the absolute and relative muscular power between groups. Results. Subjects without heart failure had significantly greater absolute (362 ± 18.5 W vs. 438 ± 22.3 W, p = 0.015) and relative (4.6 ± 0.2 W / kg vs. 5.9 ± 0.2 W / Kg, p = 0.001) muscle power versus subjects with heart failure. Conclusion. Heart failure harms the muscular power of the lower limbs in the elderly, which may influence the prognosis and evolution of the disease and capacity functional.